Analisis Pengaruh Bauran Pemasaran Terhadap Volume Penjualan Bawang Goreng Di Kota Palu - Khatima, Husnul (Mitra Sains, 2015)
This research aims to determine the effect of product, price, place and promotion Against sales volume of fried onion in Palu. The population in this research as many as 52 industry fried onions. The total sample as many as 34 industries that considered representative of the population. Data were analyzed using multiple linear analysis. The analysis showed that the value Ftest (9,815) > Ftabel (4,04), this means that the independent variable (Xi) simultaneously the effected significantly toward dependent variable (Y). The coefficient of determination (R²) equal to 0.775 atau 77,50%, which means that the industry’s sales volume fried onions (Y) may be described or explained simultaneously by the product variable (X1), price (X2), place (X3), and promotion (X4), while the remaining 22,50% is explained by other variables not included in the model.